Indicadores comportamentais, estressores e coping em adolescentes com fissura labiopalatina - Pacheco, Paula Mello (2017)
Specific stressors such as communication difficulties and facial deformity may occur for adolescents with cleft lip and palate (PFT), causing greater difficulty in psychosocial adjustment. The objective of this study was to describe behavioral, stressor and coping indicators in adolescents with cleft lip and palate (FLP), through a descriptive-comparative and cross-sectional study, with 59 adolescents of both sexes (52.5% male) 12 and 17 years (m = 14.3), 15 with FLP and 44 without FLP. Parents of adolescents with FLP participated by providing information on behavioral problems and social competence of adolescents through the Child Behavior Checklist (CBCL / 6-18 years). Adolescents responded to Youth Self-Report (YSR), stressors (Adolescents Perceived Events Scale (APES)), and coping (Coping Scale). There was a clinical profile for total behavioral problems and internalisation problems (YSR), but there were no significant differences between self-report of the adolescent with FLP and parents' reports. The analysis of coping related to "being born with FLP" and "having your secret revealed by a friend" indicated that FLP adolescents feel more challenged and welcomed in the situation of having been born with a fissure; and refer to more sadness, fear and anger, before "having your secret revealed by a friend". Comparative analyzes between the psychological variables of adolescents with FLP and without FLP did not find statistically significant differences. Thus, adolescents with FLP present indicators of an adaptive coping process, emphasizing the importance of behavioral evaluation and coping.